Impact of COVID-19 on the United States Economy and the Policy Response - Commission économique pour l'Amérique latine et les Caraibes (United Nations, 2020)
The outbreak of the coronavirus disease (COVID-19) pandemic has upended the global and United States economies, exacting a large human toll and shutting down major economic sectors. While there is significant uncertainty about United States economic growth prospects, the impact of the pandemic is severe. The record-long United States economic expansion came to an end as a result of the COVID-19 pandemic, with forecasts of a deep recession in 2020. The outlook remains highly uncertain, as it is difficult to gauge the social and economic impact of the pandemic, which will depend on the success of containing the outbreak and the measures to restart economic activity. The economic policy response to the COVID-19 pandemic has been substantial and immediate. Three stimulus packages were approved by the United States Congress in March to address the impact on households and businesses. New legislation was also approved in April and June to improve the effectiveness of the programmes included in the previous three fiscal packages. The United States Federal Reserve cut interest rates to the zero lower bound, offered unlimited quantitative easing and deployed old and new policy tools aimed at keeping financial markets functioning.